Chaos quasi-opposition crayfish based modified new controller designed for hybrid deregulated power environment considering cyber-attack - Singh, Pranav Prakash; Shankar, Ravi; Singh, S.N. (Chaos, solitons and fractals, 2024)
Frequency security is critical to the stability and dependability of the electrical systems. The integration of renewable energy resources presents new challenges for power networks and frequency security. In order to provide a more reliable control mechanism for improved frequency regulation in multi area deregulated environments with penetrations of renewable energy sources like Solar photovoltaic and wind system has been included considering along with its intermitance nature. Additionally, to get more realistic approach and its analysis, nonlinearities such as generation rate constant and governor dead band has been taken into consideration for the anticipated Load Frequency Control (LFC). A novel modified cascaded Dual-Loop Linear Active Disturbance Rejection based Tilted controller has been proposed for the suggested LFC paradigm. A modified version of the Chaotic Quasi-Opposition Crayfish Optimisation algorithm (CQOCOA) has been offered as a novel optimization approach for optimal parameters of the proposed controller. ITSE has been taken as objective function for optimization purpose. Moreover, a comprehensive detailed examination for the proposed LFC system has been investigated and successfully implemented. The performance has been examined under a variety of operating scenarios, including multiple-step, random load disturbances and Distributed Generation (DG) analysis along with its technical core advancements. This study has been investigated and validated over large multi area power system i.e., IEEE-118 bus system. This work also put forward the deep analysis and implementation of learning-based attack detection and mitigation method for the grid's frequency regulation with cyber-physical model. The effectiveness of the proposed controller has been compared and verified over previous published literature work of international repute. The compressive results analysis provide strong evidence in favour of effectiveness and efficacy of the proposed control methodology. Furthermore, this work also suggests its potential to implement in hybrid multi area power system for enhancing the performance and stability in deregulated power structure. •A non-linear hybrid power structure is proposed under deregulated power environment which also deals with renewable energy scenario with its different latency.•A new modified LADRCbased (2DOFTIDN) controller structure is proposed, which is suitable for the penetration of RESs and proposed system under investigation.•For the different optimal parameters of the controller, a new modified CQOCOA is proposed. The effectiveness of the suggested optimization is compared with existing meta-heuristic optimization for its superiority.•The suggested power structures are verified on large power system benchmark i.e., on modified IEEE-118 system.•The proposed power structure is also carried out for physical cyber-attacks dictation and mitigation, which enhances the utilization and effectiveness of the proposed hybrid deregulated power system.